2023
DOI: 10.3389/fgene.2023.1118391
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of ferroptosis-related genes and immune cell infiltration in thyroid associated ophthalmopathy

Abstract: Thyroid associated ophthalmopathy (TAO) is an orbital autoimmune inflammatory disease that is commonly associated with thyroid dysfunction. Although the etiology of TAO is unclear, ROS accumulation and oxidative stress have been closely linked to the pathogenesis of TAO. Ferroptosis is an iron-dependent programmed cell death characterized by intracellular labile iron levels, excessive accumulation of reactive oxygen species (ROS) and lipid peroxidation. Currently, there are few reports regarding the role of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown its association with thyroid-associated ophthalmopathy, gastric cancer, and susceptibility to glaucoma. Furthermore, it can function as a ceRNA to influence the severity of schizophrenia ( 53 - 55 ). This RNA acts as an oncogene in bladder cancer and breast cancer, but its role in ACC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown its association with thyroid-associated ophthalmopathy, gastric cancer, and susceptibility to glaucoma. Furthermore, it can function as a ceRNA to influence the severity of schizophrenia ( 53 - 55 ). This RNA acts as an oncogene in bladder cancer and breast cancer, but its role in ACC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research, the co-expression relationship of differentially expressed lncRNA and extracellular matrix related mRNA implies that lncRNA may be involved in the control of extracellular matrix remodeling in TAO orbital fat/connective tissue (31). Furthermore, the lncRNA-miRNA-mRNA network was built using high-throughput sequencing of orbital tissue, which was likewise linked to the etiology of TAO (32). LINC01140 has been shown in cell tests to control macrophage M2 polarization (33) and lessen their inflammatory response (34).…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, it was reported that Graves’ hyperthyroidism could interfere with iron metabolism and elevate serum ferritin ( 16 ). In a recent study, several ferroptosis driver genes were found to exhibit relatively low expression levels in orbital tissues of TAO patients, indicating the abnormal iron metabolism in patients with TAO ( 17 ). However, whether the brain iron concentration of TAO patients exists abnormality remains unknown.…”
Section: Introductionmentioning
confidence: 99%